Theoretical Model of Labor Patterns: Study Case Transition from Public Sector to Private Sector - Anton Abdulbasah Kamil (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2008)
In this paper we try to analyze the selection mechanism of the labor force used by the private sector.As we know the objective of a private firm is the maximization of the profit, in order to fulfill this goal,the employer has to select the necessary number of skilled and unskilled workers, according to thetechnology of production. In our model we can see the unemployment resulting from the gap betweenthe supply and the demand for labor affects only the unskilled individuals. The existence ofunemployment among qualified individuals could be explained by the fact that the selection processhas been done gradually. The higher salaries offered by the private sector determined the workers toquit prematurely their job; the supply of skilled labor was higher than the possibilities of absorbingthose resources existing in the private sector.